Investigating the misconception of students in initial algebra - H Beeh; R Rosjanuardi; A Jupri (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Misconception on algebra is one of the fundamental problems in mathematics learning. Misconception on algebra is a condition in which the student does not correctly understand and master the algebraic concept. This can cause students fail in building a correct knowledge framework, both in the concept of algebra and in other mathematical concepts using algebra. This study aims to reveal the phenomenon of misconceptions in initial algebra. A total of 52 eighth grade students from two different schools were given an algebra test and six students were interviewed afterwards. The results showed that most students made mistakes and were not correctly understanding simple algebraic forms, such as variables, coefficients and similar terms. It was concluded that students experienced some misconceptions on the basic concept of algebra.